Psychoeducational Comic Series 'Unable to Part with Them' for Mental Health in Reducing Phubbing Behavior in Generation Z Teenagers - Rosdiana, Yanti; Devi, Hilda Mazarina; Chotimah, Chusnul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Social media has emerged as the primary source of information among young users; however, its negative impact on mental health has led to addiction. The most tech-savvy generation today is Generation Z. Addiction to phones/gadgets among Generation Z teenagers is increasing in line with the growing use of social media, which in turn affects their behavior. One of the behavioral impacts is phubbing. Phubbing is the behavior of focusing on one’s phone/gadget while ignoring the person they are speaking with. The purpose of this study is to analyze the influence of phubbing behavior among Generation Z teenagers in the Tlogomas neighborhood before and after reading the psychoeducational comic series. This quantitative study uses a quasi-experimental design, with purposive sampling technique and a population of 125 respondents. A sample of 95 respondents met the inclusion and exclusion criteria, consisting of an intervention group and a control group. The measuring tool used is the General Scale of Phubbing (GPS) questionnaire. The analysis of the effect was carried out using the McNemar Test with SPSS 22. The analysis results showed a p-value of 0.000 in the intervention group (comic) and a p-value of 0.004 in the control group (leaflet), indicating a significant influence in both the intervention and control groups. Future researchers are expected to create better and more engaging innovations to reduce phubbing behavior among Generation Z teenagers, the future golden generation.